Penerapan Model Kooperatif Tipe Team Games Tournament untuk Meningkatkan Motivasi Belajar dan Sikap Sosial Siswa di SMAN 2 Banjar - Niyah, Dina Rifqo; Sriartha, I Putu Ananda; Citra, I Putu Ananda (Jurnal Pendidikan Geografi Undiksha, 2024)
This research aims to analyze the significant influence of the application of the team games tournament (TGT) type cooperative model on increasing students' learning motivation and social attitudes, analyze the significant influence of the TGT type cooperative model on students' learning motivation, and analyze the significant influence of the TGT type cooperative model on students' social attitudes. This research design uses a Quasi Experiment with Non-Equivalent Control Group Design. The experimental and control classes were determined using simple random sampling, and an equality test was carried out. Data collection was carried out using questionnaires and documentation sheets. Then, the data was analyzed using the multivariate analysis test (Manova). The research showed that the Cooperative Team Game Tournament model increased students' learning motivation and social attitudes "very well." The average scores for students learning motivation and social attitudes in the experimental class were 77.64 and 80.19, respectively, while in the control class, they were 67.66 and 67.26. This research concludes that the TGT type cooperative learning model significantly influences students' learning motivation and social attitudes, both partially and simultaneously.